A New Strategy for Selective Area Growth of Highly Uniform InGaAs/InP Multiple Quantum Well Nanowire Arrays for Optoelectronic Device Applications (Adv. Funct. Mater. 3/2022). (14th January 2022) - Zhang, Fanlu; Zhang, Xutao; Li, Ziyuan; Yi, Ruixuan; Li, Zhe; Wang, Naiyin; Xu, Xiaoxue; Azimi, Zahra; Li, Li; Lysevych, Mykhaylo; Gan, Xuetao; Lu, Yuerui; et al.
Abstract : Infrared Photodetectors In article number 2103057, Ziyuan Li, Lan Fu, and co‐workers develop a new crystal facet engineering strategy to achieve epitaxial growth of highly uniform InGaAs/InP multiple quantum well nanowire arrays. This leads to the demonstration of a low threshold room temperature nanowire laser and broadband infrared photodetector with high responsivity and fast response time, promising for optical communication applications.